United by White Supremacy - Christina Cavener (JAm It!, 2022)
This article explores how white women in the U.S. have centered their right to citizenship on the maintenance of white supremacy. While current scholarship primarily focuses on white male supremacy and women’s historical campaigning for citizenship, little is dedicated to establishing a connection between women’s white supremacy and their organizing efforts across the generations. Through a close examination and analysis of existing literature, I argue that different groups of women in varying spaces and times assisted to create a “whites only” citizenship by emphasizing their whiteness and femininity. Since the inception of the republic, white women have repeatedly claimed their right to agency and privilege by ideologically distancing themselves from the construct of the uncivilized, masculine, and promiscuous Black woman. They assert themselves as the “civilizing” fair sex who is educated, chaste, pure, and domestic. From the fair sex advocates of the founding era to the tradwives of today’s digital world, seemingly disparate groups of women united to advocate for a “whites only” citizenship. They used every avenue possible: violence against Black women and other people of color; wrote letters and ads; held protests and rallies; participated in grassroots organizing; built far-reaching political networks; published articles; and created social media accounts. These women teach us that white supremacy is sustained by our white women friends, relatives, colleagues, and neighbors. If we start to recognize their strategic weaponization of whiteness and femininity, we can better thwart the advancement of a “whites only” citizenship.